Characterization of Structural and Electrochromic Properties of Nanocomposite \(TiO_2-WO_3 \) Films - Ninh, Dang Hai; Thao, Tran Thi; Dinh, Nguyen Nang; Long, Pham Duy (Communications in Physics, 2014)
Using doctor-blade technique, followed by electrochemical deposition, nanocomposite WO\(_3\)-TiO\(_2\) films were prepared. Structure, morphology and composition ratio of the nanocomposite films were characterized by a comprehensive analyzing the SEM, EDX, XRD and Raman scattering results. The reversible coloration and bleaching of TiO\(_2\)/ITO and WO\(_3\)-TiO\(_2\)/ITO electrodes were demonstrated. The ECD coloration efficiency of WO\(_3\)-TiO\(_2\)/ITO was found to be much larger (55.1 cm\(^2× C^ - 1)\) than that of TiO\(_2\)/ITO (34.3 cm\(^2× C^ - 1)\). The resulting nanostructured composites enables the coloration efficiency of the WO\(_3\)-TiO\(_2\) film to be considerably improved. The results suggest a potential application of the nanocomposites of two electrochromic oxides in large-area energy-efficiency (or smart) windows.